The management of facial trauma. Issue 9 (September 2021) - McCormick, Robert Stuart; Putnam, Graham
Abstract: Facial or maxillofacial trauma occurs as a consequence of physical injury to the face and can include damage to soft tissue and bony structures either in isolation or combination. There is a male predominance with highest incidence in the age group of 20–40 years. The range of injuries include soft tissue damage, bruising, lacerations, burns and fractures of the underlying facial skeleton including the zygomatic complex, mandible, maxilla, orbit and nasoethmoidal complex. The concentration of special senses in the head and neck region means that even seemingly minor injuries can have a significant impact upon the long-term outcome for a patient. Careful assessment of an injured patient must include a full ATLS evaluation to ensure that associated potentially life-threatening injuries are not missed. This article describes the signs, symptoms and treatment of maxillofacial trauma, including management of hard and soft tissue trauma.